Antimicrobial properties of acrylic resins for dentures impregnated with silver nanoparticles - Gligorijević Nikola; Kostić Milena; Tačić Ana; Nikolić Ljubiša; Nikolić Vesna (Medicinski fakultet i Klinika za stomatologiju, Niš, 2017)
Introduction. Porosity and surface adherence of acrylates make them collectors of infectious content from the mouth. This applies particularly to cold-curable acrylates, whose structure is less compact. The aim of this study was to investigate the antimicrobial effects of cold polymerized dental acrylics after impregnation with silver nanoparticles. Material and Methods. Different concentrations (2%, 5% and 10%) of silver nanoparticles were added to the polymer components (powder) of cold polymerizing acrylate, after which disk-shaped samples, 10 mm, in diameter, were made. A disk of silver nanoparticles was used as a control for our study. Antimicrobial activity was investigated using the disc diffusion method on the two most common oral cavity infecting agents - Gram positive bacterium, Staphylococcus aureus ATCC 25923, and fungus Candida albicans ATCC 2091. The results have shown that the control sample as well as the samples of silver impregnated acrylics resins exhibit antibacterial activity. The growth zone inhibition of Staphylococcus aureus in the culture medium is proportional to the concentration of silver nanoparticles in the cold curing acrylic resin. On the other hand, the test samples did not inhibit the growth of Candida albicans in the medium. Conclusion. Silver nanoparticles in cold curing acrylic resin demonstrated antibacterial activity. Expanding their antimicrobial spectrum of activity and their potential clinical application will be the subject of the future research.